SAT0029 B cell depletion affects CD8 T cells in anca-associated vasculitis. (15th June 2017) - Néel, A; Bucchia, M; Néel, M; Rimbert, M; Agard, C; Hourmant, M; Tilly, G; Yap, M; Perrin, F; Graveleau, J; Godmer, P; Brouard, S; et al.
Abstract : Background: In anti-neutrophil cytoplasmic antibodies associated vasculitis (AAV), several clues suggest that the efficacy of B cell depletion therapy lies beyond the suppression of ANCA-producing cells and may involve the suppression of B-T cell crosstalk. However, little if any data are available regarding the impact of rituximab on CD4, regulatory T and CD8 T cells in this setting. Objectives: To compare the effect of conventional immunosuppressants (CIS) and rituximab (RTX) on 3 T cells compartments in AAV. To assess the impact of patients B cells and that of B cell depletion on CD8 T cell cytokine production. Methods: Thorough cross-sectionnal immunophenotypic analysis of CD4, regulatory T and CD8 cells of 53 patients with AAV, using polychromatic flow cytometry. A multiplex Luminex immunoassay was used to measure Cytokine/chemokine production of in vitro stimulated CD8 T cells. Active untreated AAV patients' B cells and/or CD8 T cells were cocultures for 72h with Staphylococcal Enterotoxin (Autologous and criss-cross experiments), and CD8 T cells cytokine production was then measured by flow cytometry. Results: Among CD4 T cells, we found that frequency of naïve and memory subsets and the expression of CCR5, CCR4 and CD161 were not influenced by maintenance treatment type. Similarly, total Treg frequency and Treg subsets including CD161+, Helios+, resting (CD45RA+) and memory (CD45RA-FoxP3hi) Tregs were comparable among RTX and CIS treated patients. By contrast, the type of maintenance treatment markedly influenced the CD8+ T cell compartment. Patient under B cel depletion therapy had less TEMRA (CD45RA+CCR7-) and more TEM cells than those receiving CIS, and ressembled those in long term remission off therapy. CMV seropositivity did not explained the observed diifferences. Longitudinal data confirmed that B cell depletion significantly decreased TEMRA (CD45RA+CCR7-) CD8 T cell frequency (p<0.001), whereas CIS had the opposite effect. Furthermore, we found that in vitro stimulated CD8 T cells from B cell depleted patients produced less pro-inflammatory cytokine/chemokine than those from patients treated with CIS. In coculture with B cells and SEB, patients CD8 cells coculture produced higher level of inflammatory cytokines than those from controls, but only when they were stimulated with patients' B cells. Conclusions: B cell depletion therapy has a significant impact on the CD8 T cell compartment in terms of phenotype and function. B cell can promote pro-inflammtory function of CD8 T cell in vitro. CD8 T cell are found in vasculitis lesions. These observations raise the question whether the disruption of B cell help to CD8 T cells could contribute to the dramatic efficacy of RTX. Further studies are needed to demonstrate the implication of patients' CD8 T cell in tissue damage. Disclosure of Interest: None declared